Management Of Preeclampsia / Eclampsia At The National Maternal Perinatal Institute - Guevara-Ríos, Enrique (2019)
Preeclampsia is a progressive and irreversible disease that affects multiple organs and because it will harm the mother and fetus, is responsible for a considerable proportion of maternal and perinatal deaths. Complicates 3 to 22% of pregnancies and is the second leading cause of maternal death in Peru 2013 with 38%, and the leading cause of maternal death in the National Maternal Perinatal Institute with 43%. The clinical spectrum of preeclampsia ranges from mild to severe forms. The diagnostic criteria of preeclampsia are hypertension and proteinuria, however most Proteinuria 5 g no longer considered as a criterion of severe preeclampsia. Carried out a review of the new contributions in the management of severe preeclampsia and eclampsia and the management of one of its most serious complications sucha as the liver rupture.